„Ende des Transfers – Alles aussteigen!“ - Haversath, Johann-Bernhard (Journal of Geography Education, 2006)
New Cultural Geography causes controversy about transfer. It refuses the transferability of themes and examples with gaze on high tech clusters and underlines the thesis that each of these clusters is unique. However, more exact analysis proves that this position cannot be accepted. Transfer is possible and necessary in this case, too. To avoid the risks of falsifying and misunderstanding, transfer has to follow the frame of a specific path of development. This is a construction that protects and conserves the specific profile of case studies. Moreover, this method generates other insights as well: On the one hand it opens up the whole thematic width of the object represented by the path of development; on the other hand it shows – from a meta-theoretic point of view – the mental construction of all paths of development. With regard on examples of New Urban Geography, the successful application of the concept can be demonstrated.